Intermediate and long-term adverse effects of radioiodine therapy for differentiated thyroid carcinoma – A systematic review. Issue 10 (December 2015) - Clement, S.C.; Peeters, R.P.; Ronckers, C.M.; Links, T.P.; van den Heuvel-Eibrink, M.M.; Nieveen van Dijkum, E.J.M.; van Rijn, R.R.; van der Pal, H.J.H.; Neggers, S.J.; Kremer, L.C.M.; van Eck-Smit, B.L.F.; van Santen, H.M.
Highlights: I-131 for DTC may cause salivary/lacrimal gland dysfunction, transient gonadal dysfunction and SPM. I-131 therapy seems to have no deleterious effects on female reproductive outcomes. Adverse effects of I-131 are associated with the given cumulative I-131 activity. Abstract: Background: Treatment of differentiated thyroid carcinoma (DTC) often involves administration of radioactive iodine (I-131) for remnant ablation or adjuvant therapy. As DTC has favorable outcome and the incidence is increasing, concerns have been raised about the possible adverse effects of I-131 therapy. We systematically reviewed the literature to examine the risk of intermediate and long-term adverse effects of I-131 therapy in DTC patients. Methods: Multiple electronic databases were searched up to November 2014 for English-language, controlled studies that reported on the risk of salivary gland dysfunction, lacrimal gland dysfunction, gonadal dysfunction, female reproductive outcomes or second primary malignancies (SPM) after I-131 exposure. The certainty of the evidence found was assessed using GRADE. Results: In total, 37 articles met all inclusion criteria, no studies reporting on adverse effects after I-131 treatment focused solely on children. After exposure to I-131 for DTC, patients experienced significantly more frequently salivary gland dysfunction (prevalence range: 16–54%, moderate-level evidence), lacrimal gland dysfunction (prevalence: 11%, low-level evidence), transient male gonadal dysfunction (prevalence: 35–100%, high-level evidence), transient female gonadal dysfunction (prevalence: 28%, low-level evidence) and SPM (prevalence: 2.7–8.7%, moderate-level evidence) compared to unexposed patients. I-131 therapy seems to have no deleterious effects on female reproductive outcomes (very-low level evidence). The prevalence and severity of adverse effects were correlated to increasing cumulative I-131 activity. Conclusion: Treatment with I-131 for DTC may have significant adverse effects, which seem to be dose dependent. These adverse effects of treatment must be balanced when choosing for I-131 therapy in patients with DTC.